PENGEMBANGAN ALAT PERMAINAN EDUKATIF SMART BOX UNTUK MENINGKATKAN KEPEDULIAN LINGKUNGAN PADA ANAK USIA 5-6 TAHUN - Putri, Anggita Rachmadhani Pramasintha; Reza, Muhammad; Rakhmawati, Nur Ika Sari; Fitri, Ruqoyyah (TARBAWI:Journal on Islamic Education, 2025)
This research was based on observations and interviews at TK Islam Bakti 6. The results obtained were that there were environmental concerns, one of which was waste management. This research aims to determine the feasibility and effectiveness of using Smart box educational game tools to increase environmental awareness in children aged 5-6 years. This type of research uses Research and Development with the ADDIE model. The subjects in the study were 35 children aged 5-6 years. The results of this research show that the Smart box educational game tool is feasible and effective to use. The resulting data shows that asymp.Sig (2-tailed) is 0.000 so p < 0.05, because the results of significance are smaller than 0.05, Ho is rejected and Ha is accepted. This means that there is an average difference between the pretest and posttest, so it can be concluded that the use of Smart box educational game tools is effective in increasing environmental awareness in children aged 5-6 years.